IMPLEMENTATION OF THE RISK CLASSIFICATION PROTOCOL IN A HOSPITAL IN CEARÁ - Alves Pinheiro, Francisca Fernanda; Henrique de Sousa, Allysson; Vitória de Araújo Joaquim Gadelha, Társia; Furtado Magalhães, Selma; Gadelha Severino, Gadelha Severino; Soares Moreira Alves, Jamille (Cadernos ESP, 2024)
To describe the experience in implementing an institutional Reception with Risk Classification (ACCR) protocol at a hospital in Ceará. This is an experience report, developed in 3 stages, the first being research on protocols used in Brazil for risk classification in emergencies, the second involving team training, with these CLT nurses assigned to the emergency and the third audit application of the protocol. Professionals demonstrated satisfactory understanding of the choice of flowchart with 100% assertiveness. There was a reduction in discriminating indicators with 74% and clinical priorities with 77% compared to the results of the knowledge acquired by professionals. Analysis of indicators, such as flowchart, discriminators, clinical priorities, provided insights into professionals' knowledge and practical application during risk classification. An in-depth assessment of the reasons underlying the variation in indicators after training is suggested, enabling a more precise understanding.
Keywords: Risk Assessment; User Embracement; Clinical Protocols; Emergency Identification; Emergency Service Hospital